Functionalization of cotton fabric using bio-organic heat storage materials for human protection and thermal comfortability - Menna Zayed; Heba Ghazal; Hanan A. Othman; Eman Abd El-Aziz; Ahmed G. Hassabo (Scientific Reports)
Abstract In this work, the synthesis of smart hosting materials from modified gelatin with different fatty acids (myristic acid, palmitic acid, and stearic acid) has been observed and characterized. Coconut oil was used as a natural phase change material (PCM) and octadecanol was used as an organic phase change material. Different concentrations of Phase change materials were impregnated in modified gelatin and applied to cotton and/or dyed cotton fabric with reactive dye. The treatment process was done using two methods, first method, the fabric was pre-treated with PCM composite and then dyed with reactive dye solution, and second method, the fabric was dyed with reactive dye solution and then treated with PCM composite. Smart PCM composite based on modified gelatin produced thermo-regulating properties which are responsible for controlling body temperature. The gelatin/PCM composite and treated cotton fabric were characterized using DSC, FT-IR, and SEM. The results confirmed the synthesis of modified gelatin and also confirmed its reaction with the cotton surface. DSC results showed that the treated cotton fabric with coconut oil composite has the best thermo-regulating properties.